The Influence of Transaction-Based Satisfaction and Experience-Based Satisfaction toward Repurchase Intention with Brand Image as Mediation Variable for Virtual Hotel Operator - Kalimasada, Kalimasada; Rofiq, Ainur; Mugiono, Mugiono (Jurnal Aplikasi Manajemen, 2024)
This research investigates the factors influencing the Virtual Hotel Operator (VHO) customer's repurchase intention. This research implements transaction-based and experience-based satisfaction as the independent variables influencing repurchase intention, with brand image as the mediation variable. This research is classified as explanatory research, and the data were collected using an online survey method. The respondents comprised 200 customers who had purchased using VHO's platform of their own accord within the past year. The research data and hypothesis are analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The analysis shows that transaction-based satisfaction has a positive and significant effect on repurchase intention, while experience-based satisfaction has no positive and significant effect. The brand image also has a positive and significant effect on repurchase intention. The mediation test results indicated that brand image can play an important role in transaction-based satisfaction influence on repurchase intention, and experience-based satisfaction influence on repurchase intention.